Effects of treatment of rheumatoid arthritis patients with an antibody against tumour necrosis factor alpha on reticuloendothelial and intrapulmonary granulocyte traffic. - Taylor, P; Peters, A; Glass, D; Maini, R (1999)
The therapeutic effects of a monoclonal antibody against tumour necrosis factor alpha (TNFalpha) were evaluated objectively in 10 patients with rheumatoid arthritis by 111In-labelled granulocyte imaging before and after treatment, and compared with changes in granulocyte kinetics with respect to the liver, spleen and lungs. Anti-TNFalpha resulted in a decrease in the size of the whole-body pool of marginating granulocytes, as reflected by a significant increase in the 30 min intravascular recovery of labelled granulocytes from 40% (S.D. 10) to 47% (S.D. 16) of injected activity (P<0.02). The 111In contents of the spleen, liver and lungs were unchanged, so the origin of the increment in recovery was presumed to be a reduction in granulocyte margination in inflamed synovium, although this was not quantifiable. The sizes of the granulocyte pools in the liver and lungs, expressed as the 111In content of the organ per unit of circulating 111In-labelled cells, were not significantly different after treatment, but the splenic granulocyte pool decreased by 16% (S.D. 19) (P<0.05). Individual changes in the size of the splenic pool showed no significant correlation with corresponding changes in 30 min recovery or with corresponding indices of inflammation (24 h 111In-granulocyte joint activity and C-reactive protein). We conclude that anti-TNFalpha produces an obvious resolution in inflammatory joint activity that is accompanied by an increased circulating component of the total blood granulocyte pool, as a result of decreased margination at sites of inflammation. Anti-TNFalpha may also produce a specific decrease in splenic granulocyte pooling, independent of any anti-inflammatory effects, although a similar decrease in the lungs, which might be anticipated as a result of reduced cytokine-induced granulocyte activation, could not be detected.